Pengaruh Social Media Marketing dan Celebrity Endorsement Terhadap Minat Beli Konsumen Produk Wardah Beauty - Noor Fahmi Shihab; Purwatiningsih, Purwatingsih; Ratih Setyo Rini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to explore the effect of social media marketing and celebrity endorsement on consumer buying interest in Wardah Beauty products. The research was conducted from April to June using a quantitative approach. The research sample consisted of 100 respondents. Data analysis techniques include data quality test, classical assumption test, hypothesis testing, multiple regression analysis, and coefficient of determination test using IBM SPSS 25 software. Partial test results show that social media marketing (X1) has a significant influence on consumer buying interest (Y), with a calculated T value of 4.092> 1.661 and a significance of 0.000 <0.05. Meanwhile, celebrity endorsement (X2) has no significant effect on consumer buying interest (Y), with a T value of 1.469 < 1.666 and a significance of 0.145 > 0.05. Simultaneously, the effect of social media marketing (X1) and celebrity endorsement (X2) on consumer buying interest (Y) has been tested using the F test, which shows a significant effect with an F value of 12.771> F table 3.090 and a significance of 0.000 < 0.05. These results indicate that social media marketing (X1) and celebrity endorsement (X2) together have a positive influence on consumer buying interest (Y) in Wardah Beauty products.